Dietary Inhibitors of Histone Deacetylases in Intestinal Immunity and Homeostasis - Schilderink, Ronald; Verseijden, Caroline; de Jonge, Wouter J. (Frontiers in Immunology, 2013)
Intestinal epithelial cells are integral players in homeostasis of immunity and host defense in the gut and are under influence of the intestinal microbiome. Microbial metabolites and dietary components, including short chain fatty acids (acetate, propionate and butyrate; SCFAs), have an impact on the physiology of intestinal epithelial cells at multiple levels, including the inhibition of deacetylases affecting chromatin remodeling and global changes in transcriptional activity. The number and diversity of butyrate-producing bacteria is subject to factors related to age, disease and to diet. At physiological levels, SCFAs are inhibitors of histone deacetylases (HDACs) which may explain the transcriptional effects of SCFAs on epithelial cells, although many effects of SCFAs on colonic mucosa can be ascribed to mechanisms beyond HDAC inhibition. Interference with this type of post-translational modification has great potential in cancer and different inflammatory diseases, because HDAC inhibition has anti-proliferative and anti-inflammatory effects in vitro, and in in vivo models of intestinal inflammation. Hence, the influence of dietary modulators on HDAC activity in epithelia is likely to be an important determinant of its responses to inflammatory and microbial challenges.